Life Blood - Hoover, Thomas, 1941- (Salt Lake City, UT : Project Gutenberg, 2010)
"Life Blood" by Thomas Hoover is a contemporary novel written in the early 21st century that blends elements of a medical thriller with themes of personal struggle and adoption. The story centers around Morgan James, a filmmaker who finds herself entangled in a dark conspiracy involving bizarre human experimentation while navigating her own infertility issues and the complex world of adoption. The opening of the novel introduces Morgan as she experiences the tinges of mid-life regret and a desire for family, juxtaposed against her dedication to completing her feature film, "Baby Love." In the midst of this creative endeavor, she embarks on an interview with a woman, Carly Grove, who shares her adoption story that seems too good to be true. Morgan's longing for a child intensifies as her own dreams of motherhood fade, leading her to contemplate adoption. The narrative hints at ominous forces at play, particularly concerning the adoption agency, Children of Light, adding a layer of suspense as Morgan seeks to uncover the truth behind her characters' stories. (This is an automatically generated summary.)
Release date is 2010-11-14
Produced by Al Haines
Keywords: Horror tales; Suspense fiction; Central America -- Fiction; Adoption -- Corrupt practices -- Fiction; Human experimentation in medicine -- Fiction